Teacher's Efforts in Improving Kihondachi Basic Techniques through Static Balance Training in Kata Number - Cindy Lestari , Astri; Angga Permadi, Asep; Ramadhana Sonjaya, Azhar (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Balance has an influence in the world of sports because balance is one of the factors of physical fitness. Research conducted previously stated that basic techniques in martial arts required balance and many were in the sufficient category. So there needs to be a teacher's effort to improve the balance. In the world of karate martial arts, the basic technique of kihon dachi requires good balance, so this study aimed to improve the basic technique of kihondachi in kata numbers. Materials and Methods. The method used in this study was the experimental method because this study aimed to compare events caused by certain treatments and also to determine Static Balance in playing karate number kata. The research design used a pretest posttest. The population of this study were extracurricular athletes at SMAN 3 GARUT with a total of 30 people and a sample of 15 people. The research instrument used in this study was the Kihon Dachi Test for Static Balance. Results. It was found that the sig (2-tailed) value was 0.000 <0.05, so it can be concluded that there was a significant difference in the results of static balance training on pretest and post-test data. The results of the data above can be concluded that there was a significant effect of the Static Balance exercise programme on the number of Kata. With average pre and post-test scores for kihondachi (52.89-75.56), and kata (48.64-69.28). Thus, this training program was an attempt to improve the basic technique of kihondachi in kata numbers that are suitable for such improvement. Conclusion. Based on the results of the data calculation, it can be concluded that this training program is an attempt to improve the basic kihondachi technique in kata and is suitable for improving the training.